Constraints to Acquisition of Entrepreneurial Skills in Garment Making by Undergraduates: A Case Study of Ignatius Ajuru University of Education, Port Harcourt, Rivers State - L. L., Onorhiere; Minaseichinbo, Bamson (Journal of Home Economics Research, 2024)
The study focused on constraints to acquisition of entrepreneurial skill in garment making by undergraduates of Ignatius Ajuru University of Education (IAUni Ed) Rumuolumeni Campus, Port Harcourt, Rivers State as a case study. Specifically, the study identified students, teachers and school/ facilities related constraints to acquisition of entrepreneurial skills in garment making, as well as strategies that could be applied to ameliorate the constraints. It adopted survey research design. Populations for the study consistedt of all lecturers and undergraduate of Department of Home economics IAUni Ed. Questionnaire was used for data collection. Mean were used for data analysis. Major findings include 11 students -related constraints, including among others, lack of interest pattern drafting lack of funds for practical work, 12 teachers-related constraints, including insufficient number of clothing and textile lecturers, lack of in-service training for teachers to upgrade experiences; 17 school / facilities-related constraints, including lack of funds from school authorities to carry out projects in clothing and textiles laboratory, lack of entrepreneurial development center for acquiring skills in garment making in the school among other; 24 strategies that could be applied to ameliorate the constraints. These include establishment of entrepreneurial development center in garment making in the school, provision for excursions and field trips for students, employment of more clothing and textiles lecturers, sewing industries should provide opportunities for undergraduates, industrial training among others. Recommendations include that lecturers should encourage students and arouse their interest in garment making, take students out for field trips, government should employ more professional clothing and textile lecturers and provide funds to assist students practical work.